Lung adenocarcinoma relapse with emerging EGFR mutation following complete response of small cell lung cancer warrants routine re-biopsy: A case report - Zhang, Minna; Tang, Yi; Wang, Junlei; Liu, Qian; Xia, Bing (Frontiers in Oncology, 2022)
Transformation of small cell lung cancer (SCLC) to lung adenocarcinoma (LUAD) is rarely reported. Here, we report a case initially presented with SCLC and was diagnosed as LUAD when the lesion relapsed at the same site. A 56-year-old patient with SCLC who received etoposide and cisplatin chemotherapy combined with radiotherapy achieved a complete radiological response. After 28 months of stable disease, a computed tomography scan revealed a new lesion at the same site as the primary tumor. Pathological examination suggested a LUAD with an emerging EGFR exon 19 deletion. The patient was then treated with icotinib and achieved a near-complete radiological response. Nineteen months later, the patient developed resistance caused by EGFR T790M mutation and received treatment with osimertinib. At the last follow-up in January 2022, the patient was symptom-free. This case warrants re-biopsy and genetic testing as a routine operation when SCLC relapses at the same site as the primary tumor for an extended period, and prospective investigation is required.